Ideologi perjuangan dalam puisi Kita Adalah Pemilik Sah Republik Ini karya Taufik Ismail - Wiwit Nur Fatyimah Nur Fatyimah; Berliana Handini Hanif; Sapto Darsono; Dewi Kusumaningsih (Universitas Asahan, 2023)
Poetry can be interpreted as a literary work that has an effective form and is usually used as material for social criticism. Literary works by Taufik Ismail describe many socio-critical issues in the life of Indonesian society. This study aims to describe the thoughts of struggle contained in the poem We Are the Legitimate Owners of the Republic of Indonesia by Taufik Ismail. The method used in this study is descriptive qualitative which originates from a poem by Taufik Ismail We Are the Legal Owners of the Republic of Indonesia. This poem was published in 1966. The results of this research show that there is a meaning that humans must have for struggle, namely to rise up, be enthusiastic, not easily give up and always lead to positive and quality things.